2003
DOI: 10.1159/000073862
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Tocopherol and NADPH in the Erythrocytes and Plasma of Multiple Sclerosis Patients

Abstract: Objectives: To investigate the influence of interferon-β-1b (INF-β-1b) therapy on blood antioxidants (α-tocopherol and NADPH) in multiple sclerosis (MS). Patients and Methods: Patients with relapsing-remitting MS (n = 14) have been studied during 6 months of INF-β-1b therapy. α-Tocopherol was determined by HPLC and UV or electrochemical detection; NADPH was quantified spectrophotometrically. Results: The erythrocyte α-tocopherol level was reduced (p < 0.001) before treatment, but had regained the control level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…39 In the IFN-␤ treated group, lipid peroxidation was found to decrease to the preinjury levels. IFN-␤ treatment has been demonstrated to increase the ␣-tocopherol component of plasma nonenzymatic antioxidant mechanism in patients with MS. 17 Furthermore, IFN-␤-1b treatment has also been shown to exert a sparing effect on erythrocyte ␣-tocopherol concentration in patients with MS. 17 It is possible that IFN-␤ treatment may increase the nonenzymatic antioxidant mechanism of blood after spinal cord injury in rats. Since free oxygen radical production by neutrophils have been reported to become more important than the other sources with longer periods of cerebral ischemia, it is also possible that decreased neutrophil infiltration may result in decreased lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 In the IFN-␤ treated group, lipid peroxidation was found to decrease to the preinjury levels. IFN-␤ treatment has been demonstrated to increase the ␣-tocopherol component of plasma nonenzymatic antioxidant mechanism in patients with MS. 17 Furthermore, IFN-␤-1b treatment has also been shown to exert a sparing effect on erythrocyte ␣-tocopherol concentration in patients with MS. 17 It is possible that IFN-␤ treatment may increase the nonenzymatic antioxidant mechanism of blood after spinal cord injury in rats. Since free oxygen radical production by neutrophils have been reported to become more important than the other sources with longer periods of cerebral ischemia, it is also possible that decreased neutrophil infiltration may result in decreased lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant human interferon-beta (IFN-␤) is a regulatory cytokine with anti-inflammatory properties that has been approved for the treatment of multiple sclerosis (MS). [12][13][14][15][16][17][18][19][20][21][22][23][24] More recent experimental studies have been demonstrated that IFN-␤ possessed significant neuroprotection after transient ischemic stroke. [25][26][27] Immunomodulation with IFN-␤ has been the subject of extensive studies, but according to our literature search, the neuroprotective effect of IFN-␤ after spinal cord injury (SCI) has not yet been studied.…”
mentioning
confidence: 99%
“…IFNB treatment was associated with higher concentrations of alpha-tocopherol in plasma of MS patients compared to controls [9], and also with normalization of the alpha-tocopherol levels in erythrocytes [10].…”
Section: Introductionmentioning
confidence: 85%
“…Interferon-beta-1b therapy increased the level of alpha-tocopherol, but not the corrected lipid levels after two months of therapy [127]. After six months of interferon-β therapy, the earlier decreased α-tocopherol levels were normalized in the erythrocytes of MS patients, while the α-tocopherol/lipid ratios remained constant [137]. This finding was supported by another study, where, besides the increased alpha tocopherol levels during interferon-beta treatment, reduced disease activity on MRI was described [138].…”
Section: Redox Disturbances In Eae and Msmentioning
confidence: 99%